Thioglycolic Acid as an Amperometric Reagent for Trace Determination of Co(II) and Ni(II) - DEVI, REKHA; KHATKAR, S.P. (Asian Journal of Chemistry, 2010)
Amperometric determinations of Co(II) and Ni(II) have been carried out successfully with the help of thioglycolic acid (TGA) at d.m.e. in 0.1 M NH3 + 0.1 M NH4Cl supporting electrolyte. Metal species-TGA molar stoichiometric ratios of 1:1 for Ni(II) and 1:2 for Co(II) have been obtained using metal ions solutions as titrant (anodic titrations). Both methods seem to be the consequence of complexation reaction between the acid and the respective metal ions. Solutions as dilute as 5.86 ppm [Ni(II)] and 2.94 ppm [Co(II)] have been estimated with high degree of accuracy. Tolerance limits for foreign ions have also been worked out.